French Horn Students’ Performance Improvement and Their Perceptions of Learning through Synchronous Virtual Classroom: An Empirical Research at Hunan Normal University - Chen, Xinzhu; Cleesuntorn, Athipat (Scholar: Human Sciences, 2023)
Synchronous virtual classroom has been widely used by universities as an alternative teaching method under the covid-19 pandemic, however, in the world of French horn education, there is a lack of scholarly attention on discovering how synchronous virtual classroom could affect students’ performance improvement and perceptions. The purpose of this study is to use a synchronous virtual classroom course to assess the sample participants’ performance improvement and perceptions; and then to analyze and evaluate the results from the assessment. This study used a paired sample t-test analysis to investigate whether this learning approach has caused significant improvement on students’ performances; and used a questionnaire analysis and a template analysis based on data collected from interviews to investigate how the students think about the course, and to explore the potential benefits and drawbacks that this learning approach has. The main research findings of this study indicate that, in terms of performance improvements, synchronous virtual classroom significantly improved French horn students’ overall performance improvement; in terms of students’ perceptions, such a learning method is mentally acceptable by the students, in which they were generally satisfied with this learning approach.